The Factors Influence to Incidence of Hypertension in Baucau Municipality, Republica Democratica de Timor Leste - Joaquim Pinto; Ostelino da Silva Belo; Alexandra Maria Pires; Manuel da Costa Fernandes; Acacio Guteres Pereira; Eduardo C. Gaio; Serafina Casilda Freitas Belo (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: Hypertension is a serious problem in public health programs that affects individual health, and can affect the body and kill people. High blood pressure, also called hypertension, is blood pressure that is higher than normal. Blood pressure changes throughout the day based on your activity. Having a blood pressure measurement consistently above normal can lead to a diagnosis of high blood pressure or hypertension. Hypertension is known as a killer disease and a heterogeneous group of diseases. The ministry of health of timor leste, stated that the incidence of hypertension was 41.66% and cases of death were 27% of hospitalized patients. Method: this study used quantitative and quantitative methods together, in particular a prospective population study in the municipality of baucau where interviews with the head of the family or someone else takes the responsibility. Results and discussion:  the results of data analysis using pearson product moment with p-value 0.000 <0.05 is a stress factor that affects the cause of hypertension. Also salt consumption is 0.741 between the interval coefficients 0.60 - 0.799 classified as severe hypertension). Other tests also showed that alcohol consumption had an effect on the incidence of hypertension because the p-value was 0.466 > 0.05.   Conclusion: based on the results of data analysis, stress factors, salt and alcohol consumption have an effect on the incidence of hypertension in the people of baucau city, timor leste